A new type of recycled concrete surface layer and a construction method thereof
Patent Information
- Application Number
- CN202611503662.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0020]本发明的优点在于:本发明实现了再生骨料的高效率资源化再利用,使所得再生混凝土新型面层具有强度高和耐久性好且密实、平整、抗滑、耐磨、抗车辙、抗开裂、抗水损、低透水性的特征;实现利用工业废渣作为胶结材料完全替代硅酸盐系列水泥,使固化剂利用效率大幅度提高,助力解决我国堆填尾矿等固废的综合利用问题;实现了面层的低碳制备,节约了传统建筑材料消耗,减少了材料运输量,降低了工程成本,为我国道路、机场、堆场等基础设施提供一种低碳、环保、经济的新型面层。
Abstract
Description
Technical Field
[0001] This invention relates to a novel surface layer of recycled concrete and its construction method, belonging to the field of transportation engineering. Background Technology
[0002] Crushing and screening construction waste to prepare recycled aggregates can not only reduce the environmental pressure caused by construction waste emissions, but also make full use of resources and promote sustainable resource development. However, the crushing process of construction waste easily causes aggregate damage and increases the internal porosity of the aggregates, resulting in recycled concrete surface layers with insufficient strength and durability, limiting their application. The surface layers of roads, airports, and storage yards are facing a deep low-carbon and green transformation. Currently, the main surface layer materials are cement concrete and asphalt concrete. Cement production generates huge carbon emissions, asphalt is expensive and moderately toxic, harming the atmospheric environment, and the mining of crushed stone and gravel destroys a large amount of natural resources. Therefore, developing a new low-carbon, environmentally friendly, and economical surface layer is of great significance to the construction of infrastructure such as roads, airports, and storage yards in my country.
[0003] The constrained curing technology organically combines a curing agent containing an expansive component with the constrained body. Under constrained conditions, the expansive component hydrates, causing volume expansion and reducing the porosity of the solidified body, thereby improving its strength. Specific examples can be found in patents "Construction Method of Solidified Soil Piles" (Patent No.: ZL201610183422.6) and "Treatment Method of Contaminated Soil" (Patent No.: 201610184702.9). It is important to note that this technology uses silicate-based cement as the main binder, resulting in significant carbon emissions, and the lateral constraint of the constrained body continues throughout its service life. Furthermore, under the condition that the content of the binder and expansive component in the curing agent remains constant, the strength of the solidified body formed by combinations of binders and expansive components with different hydration rates varies significantly. Therefore, this technology cannot be directly applied to road surface layers.
[0004] Patent No. 202610815058.4, entitled "A Method for Preparing Recycled Concrete," discloses a method for preparing recycled concrete using modified recycled aggregate. Patent No. 202610802262.2, entitled "A Method for Preparing Recycled Concrete Modified with Sodium Carbonate-Carbide Slag Composite Gelation Agent," discloses a method for preparing recycled concrete by soaking recycled aggregate in a sodium carbonate solution and then electrolytically activating it to obtain modified recycled aggregate. Patent No. 202610840461.2, entitled "A Green and Low-Carbon Recycled Concrete and its Preparation Method," discloses a... The patent "Preparation of Recycled Road Building Materials Using Waste Concrete and Its Preparation and Construction Methods" (Patent No.: 200810058262.8) discloses a recycled road building material prepared using tack coat asphalt and its preparation and construction methods. The patent "A Self-Healing Semi-Rigid Base Material for Recycling Construction Waste" (Patent No.: 202010865123.7) discloses a self-healing semi-rigid base material prepared using self-healing fine aggregate. However, these patents still use traditional concrete preparation methods and all use silicate cement as the binding material. The patent "A Novel Concrete Piles for Constrained Brine Recycled Concrete and Its Construction Method" (Patent No. 202610998620.1) discloses a novel concrete pile for constrained brine recycled concrete and its construction method, which is prepared by using an expansion component to generate expansion hydrates with chloride and sulfate ions in the brine, in order to solve the problem of corrosion caused by salt ions in the brine. This is fundamentally different from the novel surface layer of recycled concrete prepared by the present invention through the self-hydration of the expansion component to produce expansion hydrates.
[0005] Based on this, the present invention proposes a novel surface layer of recycled concrete and its construction method. Summary of the Invention
[0006] This invention proposes a novel recycled concrete surface layer and its construction method, aiming to achieve high-efficiency resource recycling of construction waste and industrial waste residue, and to provide a low-carbon, environmentally friendly and economical new surface layer for infrastructure such as roads, airports and storage yards in my country.
[0007] This invention proposes a novel recycled concrete surface layer and its construction method. Specifically, the materials used to prepare the novel recycled concrete surface layer include reinforcement, recycled aggregate, curing agent, water, and admixtures. The reinforcement includes, but is not limited to, steel bars, bamboo reinforcement, fibers, and combinations of different types of reinforcement. The fibers include, but are not limited to, steel fibers, lignin fibers, synthetic fibers, and inorganic fibers. The synthetic fibers include, but are not limited to, polyacrylonitrile, polypropylene, polyamide, and polyvinyl alcohol. The inorganic fibers include, but are not limited to, basalt fibers, glass fibers, and ceramic fibers. The reinforcement ratio is 0.05-1.0%. The recycled aggregate is derived from continuously graded recycled concrete obtained by crushing and screening construction waste. Raw coarse aggregate and recycled fine aggregate, with the recycled coarse aggregate having a particle size range of 4.75~20mm and the recycled fine aggregate having a particle size range of 0.075~4.75mm. Construction waste includes, but is not limited to, waste concrete, waste sintered bricks, waste ceramic tiles, waste granite, and waste sand and gravel. The curing agent consists of a cementing component and an expansion component. A material with a slow hydration rate is used as the cementing component of the curing agent, while a material with a rapid hydration and expansion rate is used as the expansion component. When the expansion component is fully hydrated, the hydration completion rate of the cementing component is ≤25%. The mass ratio of the cementing component and the expansion component in the curing agent is 3:1. 0~80: 20~70; The hydration rate of the cementitious component of the curing agent is tested using known methods, including but not limited to quantitative calibration by testing the curve of the unconfined compressive strength of specimens prepared from the cementitious component as the curing age gradually increases; The hydration rate of the expansion component of the curing agent is tested using known methods, including but not limited to quantitative calibration by testing the curve of the volume of specimens prepared from the expansion component as the curing age gradually increases; Admixtures include but are not limited to water-reducing agents, pumping agents, air-entraining agents, waterproofing agents, rust inhibitors, antifreeze agents, etc.; The mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures ranges from 1 to 8. .2:3~8.8:2~6.8:0.3~4.0:0.1~0.6; Reinforcing materials, curing agents, recycled coarse aggregate, recycled fine aggregate, water, and admixtures are mixed evenly in proportion, spread, and shaped through a certain process. After initial compaction, secondary compaction, and final compaction, the mixture is rolled and cured under constrained load for 14 days before the constraints are removed to obtain a new type of recycled concrete surface layer. The new type of recycled concrete surface layer has the characteristics of high strength, good durability, density, flatness, anti-slip, wear resistance, rutting resistance, crack resistance, water damage resistance, and low permeability. It can realize the efficient resource utilization of construction waste and the low-carbon preparation of the surface layer, significantly saving the engineering cost of the surface layer.
[0008] When the reinforcing material described in this invention is steel bar or bamboo bar, the corresponding reinforcement ratio refers to the sum of the reinforcement ratios of longitudinal and transverse reinforcing materials. The corresponding molding process involves mixing the curing agent, recycled coarse aggregate, recycled fine aggregate, water, and additives in a specific ratio, spreading them evenly, and placing the longitudinal and transverse reinforcing materials within the layer, then compacting them. When the reinforcing material is fiber, the corresponding reinforcement ratio refers to the ratio of fiber mass to the total mass of the prepared material. The corresponding molding process involves mixing the fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and additives in a specific ratio, spreading them evenly, and then compacting them. When the reinforcing material is a combination of steel bar or bamboo bar and fiber, the corresponding reinforcement ratio refers to the sum of the reinforcement ratios of longitudinal and transverse reinforcing materials plus the ratio of fiber mass to the total mass of the prepared material. The corresponding molding process involves mixing the fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and additives in a specific ratio, spreading them evenly, and placing the longitudinal and transverse reinforcing materials within the layer, then compacting them.
[0009] The cementing component of this invention is a material with a slow hydration rate, and the cementing hydrates produced by its hydration include, but are not limited to, hydrated calcium silicate, hydrated calcium aluminate, and hydrated calcium aluminosilicate. The cementing component is composed of cementing materials and activators, with the mass ratio of cementing materials and activators in the cementing component being 75~100:0~25. The cementing materials include, but are not limited to, one or more combinations of slag, copper slag, steel slag, phosphorus slag, fly ash, coal gangue, silica fume, red mud, bottom ash, rice husk ash, calcined ash, kiln ash, and desulfurization slag. The activator is an alkaline activator, including, but not limited to, one or more combinations of quicklime, hydrated lime, activated magnesium oxide, carbide slag, sodium hydroxide, and hydrated sodium silicate.
[0010] The expansion component of this invention is a rapidly hydrating expansion type material, and the expansion hydrates produced by its hydration include, but are not limited to, ettringite, monosulfide calcium sulfoaluminate, etc.; the expansion component includes, but is not limited to, a mixture composed of aluminum-containing waste residue, alkaline waste residue, gypsum waste residue, or sulfate waste residue, etc. When a combination of aluminate cement, quicklime, and gypsum is used, the corresponding mass ratio of the three is in the range of 9~12:6~8:24~30.
[0011] The longitudinal reinforcement described in this invention is arranged within 1 / 3 to 1 / 2 of the thickness below the top surface of the surface layer, and the transverse reinforcement is located below the longitudinal reinforcement.
[0012] The curing under constrained load described in this invention refers to setting a constrained load on the surface of recycled concrete after compaction. The method includes, but is not limited to, laying a rigid plate on the surface of the compacted recycled concrete and covering the upper surface of the rigid plate with a soil layer of equal thickness or uniformly loading it.
[0013] The compaction described in this invention refers to the compaction of recycled concrete using vibratory compaction machinery, with a compaction rate ranging from 1 to 6 km / h. The specific compaction machinery, compaction rate, number of compaction passes, and constraint load value are selected based on the design value of the 14-day unconfined compressive strength of the new surface layer of recycled concrete.
[0014] The cementing component described in this invention requires the selection of an activator based on the hydration rate of the cementing component design, and the specific ratio of cementing material and activator in the cementing component is determined through preliminary experiments.
[0015] The expansion component described in this invention needs to be determined according to the chemical equation for the formation of expansion hydrates and the known calculation method to determine the specific proportion of each component material in the expansion component.
[0016] The curing agent described in this invention comprises industrial-grade materials, all of which have a specific surface area greater than 200 m². 2 / kg of powder.
[0017] The water referred to in this invention refers to drinking water that meets the "Standards for Drinking Water Quality" (GB 5749-2022). When non-drinking water is used, a comparative test should be conducted with drinking water.
[0018] The application scope of the novel recycled concrete surface layer described in this invention includes, but is not limited to, projects such as highways at all levels, urban roads, airport runways, sports fields, and large-area storage yards.
[0019] The construction process of the novel recycled concrete surface layer described in this invention is as follows: First, based on the design value of the 14-day unconfined compressive strength of the new surface layer of recycled concrete, the type of reinforcement and reinforcement ratio are determined, the mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water and admixture are determined, the material composition and proportion of the cementing component and expansion component in the curing agent are determined, and the compaction machinery, compaction rate, number of compaction passes and constraint load value are determined. Secondly, select the corresponding process according to the type of reinforcement material, mix the reinforcement material, curing agent, recycled coarse aggregate, recycled fine aggregate, water and admixture in proportion, spread them evenly, and form them through the corresponding process. Then, use rolling machinery to complete the rolling through initial rolling, intermediate rolling and final rolling according to the set rolling speed and number of rolling passes. Set the constraint load on the surface of the rolled recycled concrete and cure it under the constraint conditions for 14 days. After the constraint is removed, a new type of recycled concrete surface layer is obtained. Finally, the unconfined compressive strength of the new recycled concrete surface layer was tested. When longitudinal continuous reinforcement was provided, the average crack width, average crack spacing, and reinforcement stress at the cracks needed to be examined.
[0020] The advantages of this invention are as follows: This invention achieves high-efficiency resource utilization of recycled aggregates, resulting in a novel recycled concrete surface layer with high strength, good durability, density, smoothness, anti-slip properties, wear resistance, rutting resistance, crack resistance, water damage resistance, and low permeability; it enables the complete replacement of silicate-based cement with industrial waste residue as a binder, significantly improving the utilization efficiency of curing agents and helping to solve the comprehensive utilization problem of solid waste such as tailings in my country; it achieves low-carbon preparation of the surface layer, saving traditional building material consumption, reducing material transportation volume, and lowering engineering costs, providing a low-carbon, environmentally friendly, and economical new surface layer for infrastructure such as roads, airports, and storage yards in my country. Detailed Implementation
[0021] The following detailed description of a novel recycled concrete surface layer and its construction method according to the present invention is provided with specific embodiments. However, the application forms and scope of the novel recycled concrete surface layer provided by the present invention are not limited to this.
[0022] Example 1 A certain highway plans to adopt the novel recycled concrete surface layer and its construction method described in this invention. The design value of the 14-day unconfined compressive strength of the novel recycled concrete surface layer is 40 MPa.
[0023] The reinforcement type was determined to be fiber-reinforced concrete, with a reinforcement ratio of 0.55%. Steel fiber was selected as the fiber, waste concrete was used as the recycled aggregate, and water-reducing agent was used as the admixture. The mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixture was 3.6:5.7:4.8:2.5:0.22. The curing agent composition, calculated by weight, was as follows: cementing component: 7.5 parts red mud, 2.5 parts hydrated lime; expansion component: 2.6 parts aluminum-containing waste residue, 1.8 parts alkaline waste residue, and 6.6 parts gypsum-based waste residue. The compaction equipment was determined to be an LG520D vibratory roller, with a compaction rate of 3 km / h, 5 passes, and a constraint load of 35 kPa. Fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures were mixed evenly in proportion, spread evenly, and compacted using a rolling mill at a set rolling rate and number of passes. After initial compaction, intermediate compaction, and final compaction, a restraint load was applied, and the recycled concrete was cured under restraint conditions for 14 days. The restraint load was then removed to obtain a new type of recycled concrete surface layer. Testing showed that the performance of the new recycled concrete surface layer met the requirements.
[0024] Example 2 An airport project plans to adopt the novel recycled concrete surface layer and its construction method described in this invention. The design value of the 14-day unconfined compressive strength of the novel recycled concrete surface layer is 55 MPa.
[0025] The reinforcement type was determined to be a combination of steel bars and fibers, with a reinforcement ratio of 0.93%. Both longitudinal and transverse reinforcement were selected as HRB400 φ12 threaded steel bars, steel fibers were chosen, recycled aggregate was waste granite, and the admixture was a rust inhibitor. The mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixture was 5.3:8.6:6.2:3.0:0.1. The composition of the curing agent, calculated by weight, was as follows: cementing component: 5.5 parts silica fume, 3.5 parts desulfurization slag, 1.0 part quicklime; expansion component: 2.0 parts aluminum-containing waste residue, 1.2 parts alkaline waste residue, 4.2 parts sulfate waste residue. The compaction machine was determined to be an LG520D vibratory roller, with a compaction rate of 2 km / h, 7 passes, and a constraint load of 52 kPa. Fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures were mixed evenly in proportion and laid flat. Longitudinal and transverse reinforcements were placed within the pavement. Using a compaction machine, compaction was completed through initial, intermediate, and final compaction at a set compaction rate and number of passes. A constraint load was then applied, and the recycled concrete was cured under constraint conditions for 14 days. After the constraint load was removed, a new type of recycled concrete surface layer was obtained. Testing showed that the performance of the new recycled concrete surface layer met the requirements.
[0026] Example 3 A sports field is proposed to use a novel recycled concrete surface layer and its construction method as described in this invention. The design value of the 14-day unconfined compressive strength of the novel recycled concrete surface layer is 25 MPa.
[0027] The reinforcement type was determined to be fiber-reinforced, with a reinforcement ratio of 0.37%. Ceramic fiber was selected as the fiber, waste sand and gravel as the recycled aggregate, and antifreeze as the admixture. The mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixture was 2.3:3.6:2.4:1.2:0.2. The composition of the curing agent, calculated by weight, was as follows: cementing component: 6.0 parts fly ash, 2.5 parts red mud, 1.5 parts hydrated sodium silicate; expansion component: 6.3 parts aluminum-containing waste residue, 4.0 parts alkaline waste residue, and 12.2 parts sulfate waste residue. The compaction machine was determined to be an LG518D vibratory roller, with a compaction speed of 6 km / h, 3 passes, and a constraint load of 20 kPa. Fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures were mixed evenly in proportion, spread evenly, and compacted using a rolling mill at a set rolling rate and number of passes. After initial compaction, intermediate compaction, and final compaction, a restraint load was applied, and the recycled concrete was cured under restraint conditions for 14 days. The restraint load was then removed to obtain a new type of recycled concrete surface layer. Testing showed that the performance of the new recycled concrete surface layer met the requirements.
[0028] Example 4 A certain stockpile intends to use the novel recycled concrete surface layer and its construction method described in this invention. The design value of the 14-day unconfined compressive strength of the novel recycled concrete surface layer is 30 MPa.
[0029] The reinforcement material was determined to be bamboo reinforcement, with a reinforcement ratio of 0.6%. Both longitudinal and transverse bamboo reinforcement were selected from moso bamboo. Waste bricks were used as recycled aggregate, and a pumping agent was used as the admixture. The mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixture was 2.3:4.5:2.8:1.5:0.13. The composition of the curing agent, calculated by weight, was as follows: the binding component consisted of 6.0 parts of desulfurized slag, 3.0 parts of rice husk ash, and 1.0 part of sodium hydroxide; the expansion component consisted of 5.2 parts of aluminum-containing waste residue, 4.3 parts of alkaline waste residue, and 10.3 parts of gypsum-based waste residue. An LG518D vibratory roller was selected for compaction, with a compaction speed of 5 km / h, 5 passes, and a constraint load of 28 kPa. The curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures were mixed evenly in proportion and spread evenly. Longitudinal and transverse reinforcements were then placed within the pavement. Using a compaction machine, compaction was completed through initial, intermediate, and final compaction at a set compaction rate and number of passes. A constraint load was then applied, and the recycled concrete was cured under constraint conditions for 14 days. After the constraint load was removed, a new type of recycled concrete surface layer was obtained. Testing showed that the performance of the new recycled concrete surface layer met the requirements.
Claims
1. A novel surface layer of recycled concrete and its construction method, characterized in that: The materials for preparing the new type of recycled concrete surface layer include reinforcement, recycled aggregate, curing agent, water, and admixtures. Reinforcement includes, but is not limited to, steel bars, bamboo bars, fibers, and combinations of different types of reinforcement. Fibers include, but are not limited to, steel fibers, lignin fibers, synthetic fibers, and inorganic fibers. Synthetic fibers include, but are not limited to, polyacrylonitrile, polypropylene, polyamide, and polyvinyl alcohol. Inorganic fibers include, but are not limited to, basalt fibers, glass fibers, and ceramic fibers. The reinforcement ratio is 0.05-1.0%. The recycled aggregate is derived from continuously graded recycled coarse aggregate and recycled fine aggregate obtained by crushing and screening construction waste. The particle size range of recycled coarse aggregate is 4.75~20mm, and the particle size range of recycled fine aggregate is 0.075~4.75mm. Construction waste includes, but is not limited to, waste concrete, waste sintered bricks, waste ceramic tiles, waste granite, and waste sand and gravel. The curing agent consists of a binding component and an expansion component. A material with a slow hydration rate is used as the binding component, while a material with a rapid hydration and expansion rate is used as the expansion component. The hydration completion rate of the binding component is ≤25% when the expansion component is fully hydrated. The mass ratio of the binding component to the expansion component in the curing agent is 30~80:20~70, respectively. The hydration rate of the binding component is tested using known methods, including but not limited to quantitatively calibrating it by testing the change curve of the unconfined compressive strength of specimens prepared from the binding component with the gradual increase of curing age. The hydration rate of the expansion component is tested using known methods, including but not limited to quantitatively calibrating it by testing the change curve of the volume of specimens prepared from the expansion component with the gradual increase of curing age. Admixtures include, but are not limited to, […]. Water-reducing agents, pumping agents, air-entraining agents, waterproofing agents, rust inhibitors, antifreeze agents, etc.; the mass ratio range of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures is 1~8.2:3~8.8:2~6.8:0.3~4.0:0.1~0.6; the reinforcing material, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixtures are mixed evenly in proportion, spread, and shaped through a certain process. After initial compaction, secondary compaction, and final compaction, the mixture is rolled and cured under constrained load for 14 days before the constraints are removed to obtain a new type of recycled concrete surface layer. The new type of recycled concrete surface layer has the characteristics of high strength, good durability, density, flatness, anti-slip, wear resistance, rutting resistance, crack resistance, water loss resistance, and low permeability. It can realize the efficient resource utilization of construction waste and the low-carbon preparation of the surface layer, significantly saving the engineering cost of the surface layer.
2. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: When the type of reinforcing material is steel bar or bamboo bar, the corresponding reinforcement ratio refers to the sum of the reinforcement ratios of longitudinal and transverse reinforcing materials. The corresponding molding process involves mixing the curing agent, recycled coarse aggregate, recycled fine aggregate, water, and additives in a specific ratio, spreading them evenly, and placing the longitudinal and transverse reinforcing materials within the layer, then compacting them. When the type of reinforcing material is fiber, the corresponding reinforcement ratio refers to the ratio of fiber mass to the total mass of the prepared material. The corresponding molding process involves mixing the fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and additives in a specific ratio, spreading them evenly, and then compacting them. When the reinforcing material is a combination of steel bar or bamboo bar and fiber, the corresponding reinforcement ratio refers to the sum of the reinforcement ratios of longitudinal and transverse reinforcing materials plus the ratio of fiber mass to the total mass of the prepared material. The corresponding molding process involves mixing the fiber, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and additives in a specific ratio, spreading them evenly, and placing the longitudinal and transverse reinforcing materials within the layer, then compacting them.
3. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: The cementing component is a material with a slow hydration rate, and the cementitious hydrates produced by its hydration include, but are not limited to, hydrated calcium silicate, hydrated calcium aluminate, and hydrated calcium aluminosilicate. The cementing component is composed of a cementing material and an activator, with the mass ratio of the cementing material to the activator in the cementing component being 75-100:0-25. The cementing material includes, but is not limited to, one or more combinations of slag, copper slag, steel slag, phosphorus slag, fly ash, coal gangue, silica fume, red mud, bottom ash, rice husk ash, calcined ash, kiln ash, and desulfurization slag. The activator is an alkali activator. The expanding agent includes, but is not limited to, one or more combinations of quicklime, hydrated lime, activated magnesium oxide, carbide slag, sodium hydroxide, and hydrated sodium silicate; the expanding component is a rapidly hydrating and expanding material, and the expanding hydrates produced by its hydration include, but are not limited to, ettringite and monosulfide calcium sulfoaluminate; the expanding component includes, but is not limited to, a mixture composed of aluminum-containing waste residue, alkaline waste residue, gypsum-based waste residue, or sulfate waste residue, etc., and when a combination of aluminate cement, hydrated lime, and gypsum is used, the corresponding mass ratio of the three is in the range of 9~12:6~8:24~30.
4. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: The longitudinal reinforcement is set within 1 / 3 to 1 / 2 of the thickness below the top surface of the surface layer, and the transverse reinforcement is located below the longitudinal reinforcement. The curing under constrained load refers to setting a constrained load on the surface of the recycled concrete after compaction. The method includes, but is not limited to, laying a rigid plate on the surface of the compacted recycled concrete and covering the upper surface of the rigid plate with a soil layer of equal thickness or uniformly stacking a load. The compaction refers to compacting the recycled concrete with a vibratory compaction machine at a compaction rate of 1-6 km / h. The specific compaction machine, compaction rate, number of compaction passes, and constrained load value are selected according to the design value of the 14-day unconfined compressive strength of the new surface layer of recycled concrete.
5. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: The cementing component requires the selection of an activator based on the designed hydration rate and the determination of the specific ratio of cementing material and activator in the cementing component through preliminary experiments; the expansion component requires the determination of the specific ratio of each component material in the expansion component based on the chemical equation for the formation of expanded hydrates and according to known calculation methods; the curing agent consists of industrial-grade materials, all with a specific surface area greater than 200 m². 2 / kg of powder.
6. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: The water referred to is drinking water that meets the "Standards for Drinking Water Quality" (GB 5749-2022). When non-drinking water is used, a comparative test should be conducted with drinking water.
7. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: The application scope of the new type of recycled concrete surface layer includes, but is not limited to, highways at all levels, urban roads, airport runways, sports fields, large-area storage yards, and other projects.
8. The novel recycled concrete surface layer and its construction method according to claim 1, characterized in that: The construction process of the new recycled concrete surface layer is as follows: ① Based on the design value of the 14-day unconfined compressive strength of the new recycled concrete surface layer, determine the type of reinforcement and reinforcement ratio, determine the mass ratio of curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixture, determine the material composition and proportion of the cementitious component and expansion component in the curing agent, and determine the compaction machinery, compaction rate, number of compaction passes, and constraint load value; ② Select the corresponding process according to the type of reinforcement, mix the reinforcement, curing agent, recycled coarse aggregate, recycled fine aggregate, water, and admixture in proportion, spread them evenly, and form them through the corresponding process. Then, use the compaction machinery to complete the compaction by initial compaction, intermediate compaction, and final compaction according to the set compaction rate and number of compaction passes. Set the constraint load on the surface of the compacted recycled concrete and cure it under constraint conditions for 14 days. After removing the constraint, the new recycled concrete surface layer is obtained. Test the unconfined compressive strength of the new recycled concrete surface layer. When longitudinal continuous reinforcement is set, the average crack width, average crack spacing, and reinforcement stress at the crack need to be checked.
Citation Information
Patent Citations
Method for preparing regenerative road material by using waste concrete and construction method thereof
CN101255044A
Construction method for stabilized soil piles
CN105780753A
Treatment method of contaminated soil
CN105834206A
Self-repairing type semi-rigid base layer material recycled from construction waste
CN112110705A
Novel restraining brine recycled concrete pile and construction method thereof
CN122562476A